Loop-mediated isothermal amplification-based microfluidic chip for pathogen detection. Issue 2 (19th January 2020) - Shang, Yuting; Sun, Jiadi; Ye, Yongli; Zhang, Jumei; Zhang, Yinzhi; Sun, Xiulan
Abstract: Due to the significant growth of food production, the potential likelihood of food contamination is increasing. Foodborne illness caused by bacterial pathogens has considerably increased over the past decades, while at the same time, the species of harmful microorganisms also varied. Conventional bacterial culturing methods have been unable to satisfy the growing requirement for food safety inspections and food quality assurance. Therefore, rapid and simple detection methods are urgently needed. The loop-mediated isothermal amplification (LAMP) technology is a highly promising approach for the rapid and sensitive detection of pathogens, which allows nucleic acid amplification under isothermal conditions. The integration of the LAMP assay onto a microfluidic chip is highly compatible with point-of-care or resource-limited settings, as it offers the capability to perform experiments in combination with high screening efficiency. Here, we provide an overview of recent advances in LAMP-based microfluidic chip technology for detecting pathogens, based on real-time or endpoint determination mechanisms. We also discuss the promoting aspects of using the LAMP technique in a microfluidic platform, to supply a guideline for further molecular diagnosis and genetic analysis.